Attention Based Energy Demand Forecasting in Smart Grid Environments - Işıkdemir, Yunus Emre; Akal, Fuat (Fırat Üniversitesi, 2024)
The smart grid is a crucial aspect of the modern energy landscape, providing a reliable, efficient, and sustainable way of meeting the growing energy demands. However, the vast amounts of data generated by smart grid technology necessitate the development of advanced data processing and analysis techniques. In this paper, we propose an attention-based time series workflow that combines dilated convolution and attention mechanisms for time series forecasting in smart grid applications. This workflow extracts temporal features from time series data using dilated convolutions and emphasizes significant temporal points in the hidden states using attention mechanisms. Experimental evaluations showed up to an 8% better performance for energy demand forecasting compared to commonly used deep learning-based methods. Our workflow achieved this gain by requiring 1/3 of the training time other models took. We also improved performance by 42% in various domains, demonstrating the adaptability of our approach across different areas. This study may assist researchers in constructing accurate forecasting models for smart grid environments. Furthermore, it highlights that the attention-based approach can be employed to promote sustainable energy and optimize smart grid environments.

Akıllı şebeke, modern enerji peyzajının kritik bir unsuru olup, artan enerji taleplerini karşılamak için güvenilir, verimli ve sürdürülebilir bir yol sağlamaktadır. Bununla birlikte, akıllı şebeke teknolojisi tarafından üretilen büyük miktardaki veri, gelişmiş veri işleme ve analiz tekniklerinin geliştirilmesini gerektirmektedir. Bu makalede, akıllı şebeke uygulamalarında zaman serisi tahmininde kullanılmak üzere, dilatasyonlu konvolüsyon ve dikkat mekanizmalarını birleştiren bir dikkat tabanlı zaman serisi iş akışı öneriyoruz. Bu akış, dilatasyonlu konvolüsyonları kullanarak zaman serisi verilerinden zamansal özellikler çıkarır ve dikkat mekanizmalarını kullanarak gizli durumlardaki önemli zaman noktalarını vurgular. Deneysel değerlendirmeler sonucunda, enerji talebi tahmininde, yaygın olarak kullanılan derin öğrenme tabanlı yöntemlere göre %8'e kadar daha iyi bir performans gösterdiği gözlemlendi. Bu kazancı diğer modellerin aldığı eğitim süresinin yalnızca 1/3'ü kadar bir sürede elde edilmiştir. Ayrıca, tamamen farklı bir alanda %42'lik bir kazanç elde edilmiştir ve akışın diğer alanlara uyarlanabileceği gösterilmiştir. Bu çalışma, araştırmacılara akıllı şebeke uygulamaları için daha doğru ve verimli tahmin modelleri geliştirmelerine yardımcı olabilir, ayrıca enerji sistemlerinin sürdürülebilir yönetimi ve akıllı şebeke operasyonlarının optimizasyonu için yapay zeka ve dikkat tabanlı tahmin tekniklerinin potansiyeli hakkında değerli bilgiler sunabilir.
Akıllı Şebeke Ortamlarında Dikkat Tabanlı Enerji Talep Tahmini
Keywords: Software Engineering (Other); Yazılım Mühendisliği (Diğer)